2022
DOI: 10.1155/2022/3971967
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Marine Traditional Chinese Medicine in Pharmacopoeia of the People’s Republic of China: Development, Differences, and Trends Directions

Abstract: Background. Marine traditional Chinese medicine (MTCM) is a class of traditional medicine that has antitumor, anti-inflammatory, and antiviral properties. Bibliometric approaches were used in this study to conduct systematic research in order to gain a complete picture of MTCM research around the world. Methods. CiteSpace and NoteExpress software were utilized as tools to examine the information about authors, sources, keywords, etc. Chinese publications were collected from the CNKI, VIP, and WANFANG databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In recent years, traditional Chinese medicine has demonstrated efficacy in depression management, characterized by its favorable safety profile, consistent efficacy, minimal toxicity and adverse effects, and cost-effectiveness 18 . Notably, Codonopsis pilosula, derived from the dry roots of Platycodonaceae Codonopsis pilosula, Suhua Codonopsis pilosula and Sichuan Codonopsis pilosula, exhibits various pharmacological benefits such as anti-stress, anti-aging, gastroprotective, anti-fatigue, and anti-hypoxic properties attributed to its antioxidant effects 11,12 . This study employs network pharmacology in conjunction with molecular docking techniques to elucidate the intricate network interactions of LBT in the context of antidepressant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, traditional Chinese medicine has demonstrated efficacy in depression management, characterized by its favorable safety profile, consistent efficacy, minimal toxicity and adverse effects, and cost-effectiveness 18 . Notably, Codonopsis pilosula, derived from the dry roots of Platycodonaceae Codonopsis pilosula, Suhua Codonopsis pilosula and Sichuan Codonopsis pilosula, exhibits various pharmacological benefits such as anti-stress, anti-aging, gastroprotective, anti-fatigue, and anti-hypoxic properties attributed to its antioxidant effects 11,12 . This study employs network pharmacology in conjunction with molecular docking techniques to elucidate the intricate network interactions of LBT in the context of antidepressant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a systematic exploration and elucidation of the mechanisms underpinning traditional Chinese medicine assume critical significance. Codonopsis pilosula, derived from the dried root of Codonopsis pilosula Nannf or Codonopsis tangshen Oliv, is a traditional tonic in Chinese medicine renowned for its therapeutic properties 11 . This botanical remedy is rich in sugars, alkaloids, polyacetylenes, glycosides, terpenes, and other bioactive constituents.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro cellular studies have also suggested that the water-soluble Margaritifera concha protein has a strong effect on stimulating the differentiation of bone marrow stromal cells into osteoblasts and increased osteoblast proliferation. 3 Notably, a type of sulfated polysaccharide derived from seaweed has been used clinically for cardiovascular diseases, and sodium oligomannate (GV-971), an oligosaccharide compound derived from brown algae, has been used for the treatment of Alzheimer's disease by targeting the brain-gut axis. 4 Therefore, it is of great value to discover novel compounds with diverse biological activities from MTCMs.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been used as an herbal medicine in China relieving colds, edema, nasal congestion, and rheumatoid arthritis. Ephedra has anti-inflammatory properties ( Cao et al, 2022 ). Ephedra sinica polysaccharide (ESP) exhibits a good therapeutic effect on RA ( Zheng et al, 2023 ) by reducing the lipopolysaccharide stimulated nuclear translocation of the NF-κB p65 subunit, improving the levels of RA inflammatory markers, and reducing the release of inflammatory factors (TNF-α, IL-1β, and IL-6) and NO by inhibiting the TLR4 signaling pathway ( Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%